Biogrout : pore scale bonding phenomena in saturated and unsaturated soils - Viganotti, Matteo (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2014)
In the field of biogeocivil engineering one of the most promising in-situ ground improvement technologies is represented by Microbially Induced Carbonate Precipitation (MICP). Often referred to as biogrouting, MICP ground improvement is recognised os bioaugmentation technique employed to achieve the stabilisation of a granular soil by cementing its constituent particles together through calcium carbonate bonds.
Keywords: Civil, Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin